COMPARATIVE ANALYSIS OF TRANSPIRATION IN POTATO GENOTYPES UNDER IN VITRO AND IN VIVO CONDITIONS (International Conference on Economics, Finance, Banking and Management, 2025)
This study investigated the process of transpiration in plants under in vitro (laboratory) and in vivo (natural) conditions using four genotypes: S-46, S-73, S-55, and S-17. Results demonstrated that the transpiration rate was significantly higher in vivo compared to in vitro. The highest rate was observed in genotype S-17, indicating its superior adaptability to environmental stresses such as drought and salinity. The study highlights the importance of understanding plant water regulation mechanisms under varying conditions and presents genotype S-17 as a promising candidate for cultivation in arid and saline soils.